Fetal foot length at delivery as a tool for determining gestation length in non‐macerated stillbirths. Issue 1 (8th May 2017) - Geldenhuys, Elaine; Coldrey, Jean; Wright, Colleen; Nel, Daan; Roberts, Drucilla J.; Boyd, Theonia K.; Odendaal, Hein; ,
Abstract: Objective: To assess whether fetal foot length at autopsy could reliably indicate gestation duration at stillbirth and the effects of maceration on this method. Methods: The present cross‐sectional secondary analysis was part of the Safe Passage Study; all Safe Passage Study participants who experienced a stillbirth at Tygerberg Academic Hospital, Cape Town, South Africa, between August 1, 2007, and January 31, 2015, were eligible to participate. After providing written informed consent for autopsy, the duration of gestation calculated using early ultrasonography and fetal foot length were compared. Results: There were 69 fetal autopsies included in the present study; placental histology was available for 65. Generally, the gestation length calculated from the first ultrasonography scan correlated well with that calculated from the fetal foot length (Spearman correlation=0.85). However, significant differences were found in the gestation lengths calculated when the fetus was macerated ( P< 0.001), or when umbilical cord pathology ( P< 0.001) or maternal vascular malperfusion ( P< 0.001) was the cause of fetal death. Conclusion: Foot length at stillbirth was a good indicator of gestation length; however, it was a weaker indicator if fetal maceration had occurred. Abstract : A correlation was found between using early ultrasonography and fetal foot length to calculate the length of gestation at stillbirth; fetal maceration compromised this.